2012
DOI: 10.1007/s10529-012-0978-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural classification of biotin carboxyl carrier proteins

Abstract: We gathered primary and tertiary structures of acyl-CoA carboxylases from public databases, and established that members of their biotin carboxylase (BC) and biotin carboxyl carrier protein (BCCP) domains occur in one family each and that members of their carboxyl transferase (CT) domains occur in two families. Protein families have members similar in primary and tertiary structure that probably have descended from the same protein ancestor. The BCCP domains complexed with biotin in acyl and acyl-CoA carboxyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
(3 reference statements)
0
16
0
Order By: Relevance
“…Among the subunits of heteromeric ACCase, BCCP subunit interacts with BC and accepts a bicarbonate ion when ATP is converted to ADP, thus it can be served as the donor of activated carboxyl group, then the complex (BCCP-biotin) transfers the ion to CT, and finally produces malonyl-CoA in fatty acid biosynthesis (Ke et al, 2000; Sasaki and Nagano, 2004; Chen et al, 2012; Jang et al, 2015). Previous studies revealed that BCCP subunits have variable protein lengths, and low similarity (Qiao and Liu, 2007), while each of BCCP subunits contains a biotinylated domain located at the C-terminal region, harboring a highly conserved motif (CIIEAMKLMNEIE) (Qiao and Liu, 2007; Xuan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Among the subunits of heteromeric ACCase, BCCP subunit interacts with BC and accepts a bicarbonate ion when ATP is converted to ADP, thus it can be served as the donor of activated carboxyl group, then the complex (BCCP-biotin) transfers the ion to CT, and finally produces malonyl-CoA in fatty acid biosynthesis (Ke et al, 2000; Sasaki and Nagano, 2004; Chen et al, 2012; Jang et al, 2015). Previous studies revealed that BCCP subunits have variable protein lengths, and low similarity (Qiao and Liu, 2007), while each of BCCP subunits contains a biotinylated domain located at the C-terminal region, harboring a highly conserved motif (CIIEAMKLMNEIE) (Qiao and Liu, 2007; Xuan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The BCCP domain physically translocates between catalytic domains and assists in inserting biotin into the individual active sites. The primary sequence and tertiary structure for the C-terminal ∼80 amino acids of the BCCP domain is conserved for all enzymes within the family, suggesting that they are descended from a common ancestor [20]. In Escherichia coli acetyl-CoA carboxylase, however, the BCCP subunit includes an additional N-terminal domain of ∼80 amino acids which may serve to impede the catalytic half-reactions prior to assembly of the complete enzyme complex [21], [22].…”
Section: Biotin-dependent Enzymesmentioning
confidence: 99%
“…The Papilionoideae plastid ACCase consists of four subunits, each coded by a separate gene: biotin carboxylase (BC, gene accC ), biotin carboxyl carrier protein (BCCP, gene accB ), alpha-carboxyltransferase (a-CT, gene accA ) and beta-carboxyltransferase (b-CT, gene accD ). The genes coding three of these subunits: accC , accB , and accA , are localized in the nuclear genome whereas accD gene is localized in the plastid genome [ 51 , 52 ]. This type of enzyme forms active complex inside plastids and is named heteromeric (ht) ACCase or bacterial type ACCase.…”
Section: Introductionmentioning
confidence: 99%